1981
DOI: 10.1042/bj1960839
|View full text |Cite
|
Sign up to set email alerts
|

Induction by phenobarbital of the mRNA for a specific variant of rat liver microsomal cytochrome P-450

Abstract: The treatment of rats for 4 days with phenobarbital causes an apparent 3-fold increase in the amount of total liver cytochrome P-450. By sodium dodecyl sulphate/polyacrylamide-gel electrophoresis, metyrapone binding and immunoprecipitation, this increase was found to be due to a much larger increase in a restricted number of specific cytochrome P-450 variants. A radioimmunoassay technique demonstrated that the major phenobarbital-inducible variant, of molecular weight 52 000, is induced 24-fold by phenobarbita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 47 publications
(31 reference statements)
0
14
0
Order By: Relevance
“…The induction of P-450 2B by PB is primarily due to new 2B protein synthesis that results from an increase in steady state levels of 2B mRNA (Adesnik et al, 1981;Phillips et al, 1981). Thus, PB induction of these P-450s apparently does not involve the mRNA stabilization mechanism associated with induction of P-450 1A2 by 3-methylcholanthrene (Kimura et al, 1986;Silver & Krauter, 1988), nor does it involve protein stabilization, which contributes to the induction of 3A P-450(s) by macrolide antibiotics (Watkins et al, 1986) and the induction of P-450 2E1 by acetone (Song et al, 1989) (Table 3).…”
Section: Transcriptional Activation By Pbmentioning
confidence: 99%
“…The induction of P-450 2B by PB is primarily due to new 2B protein synthesis that results from an increase in steady state levels of 2B mRNA (Adesnik et al, 1981;Phillips et al, 1981). Thus, PB induction of these P-450s apparently does not involve the mRNA stabilization mechanism associated with induction of P-450 1A2 by 3-methylcholanthrene (Kimura et al, 1986;Silver & Krauter, 1988), nor does it involve protein stabilization, which contributes to the induction of 3A P-450(s) by macrolide antibiotics (Watkins et al, 1986) and the induction of P-450 2E1 by acetone (Song et al, 1989) (Table 3).…”
Section: Transcriptional Activation By Pbmentioning
confidence: 99%
“…Microsomal membrane vesicles were isolated from the liver of male (n = 3) or female (n = 3) wild-type or knockout mice as described earlier [31]. Microsomal vesicles from Spodoptera frugiperda (Sf) 9 cells expressing either human FMO1 or FMO3 were isolated as described earlier [33].…”
Section: Imipramine Metabolism In Vitromentioning
confidence: 99%
“…Microsomal membrane vesicles were isolated from the male (n = 3) and female (n = 3) mouse tissues as described earlier [31]. Western blotting was performed as described earlier [32].…”
Section: Quantification Of Flavin-containing Monooxygenase Proteinsmentioning
confidence: 99%
“…Various groups have shown that PB administration results in an increase in the mRNA coding for cytochrome P-450 b (90,91), and Phillips, et al (90) have estimated that there is approximately an 18 fold increase of 52 Κ cytochrome P-450 mRNA in the livers of Sprague Dawley rats. However following PB administration, it has been observed that the increase of spectrophotometrically detectable cytochrome P-450 reaches a maximum at about 45 hours after a single injection of phenobarbital whilst the increase in cell free translation of apo-cytochrome P-450 directed by the corresponding mRNA, reaches a maximum at 16 hours following PB administration (89).…”
Section: Biosynthesis Of Cytochrome P-450 Directed By Rat Liver Messementioning
confidence: 98%
“…PB and 3MC pretreatment of experimental animals results in a 2-3 fold increase in the liver microsomal content of cytochrome P-450 (26,90), and immunological measurements indicate that pretreatment with either xenobiotic inducer leads to a 24-50 fold increase in the levels of different molecular forms of cytochrome P-450, each of which is present at low levels in the liver of uninduced animals (25,26,90). PB treatment for four days was shown to result in a large increase in liver weight (55%) and although the level of polyribosomal RNA per gram of liver increased only slightly (12%), there was a marked enhancement of poly (A) + mRNA in the liver microsomal fraction (82).…”
Section: Biosynthesis Of Cytochrome P-450 Directed By Rat Liver Messementioning
confidence: 99%